Factors that Affect Farmland Conversion in China and Indonesia - Adam, Lukman; Xuefeng, Li; Jin, Jia (Asian Journal of Agriculture and Rural Development, 2018)
The first challenge in this century is to maintain or increase the farmland because land is the determinant factor. China and Indonesia have a considerable population, have the same major food crops, and have been facing a problem with farmland conversion. The problem will be focused on the following issue whether factors are affecting farmland conversion in China and Indonesia. This research used the data from The World Bank in 1982 - 2014 and used Auto-Regressive Distributive Lags (ARDL) as the data analysis. In the short-run, investment and urban population are significant variables to affect the farmland conversion in China and Indonesia. The employment merely affects for farmland conversion in China, while the agriculture GDP and railways affect for Indonesia. In the long-run, employment and railways affect farmland conversion in China; however, the agriculture GDP, investment, and urban population are significant for Indonesia. Some policies which needed to prevent farmland conversion began stipulated zoning and spatial planning in central and local government, and incentives for the farmer.